Kualitas Fisik dan Kimia Air Sumur Gali dan Sumur Bor di Wilayah Kerja Puskesmas Guntur II Kabupaten Demak - Siti Munfiah; Nurjazuli Nurjazuli; Onny Setiani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background: Preliminary study results of dug well in Sidokumpul obtained that color levels is 56 TCU, totalhardness is 998 mg/l, manganese is 5.26 mg/l, sulphate is 980 mg/l and organic matter is 14.85 mg/l. The resultsof bore well water in Blerong showed sulphate levels is 414.63 mg/l. All of these parameters have exceeded thequality standard of water.Method: This was an observational research with cross sectional design. Sampling was done by purposivesampling. The number of samples were 40 wells consist of 20 dug wells and 20 bore wells. Bivariate analysis usedSPSS and multivariate analysis used SEM VPLS.Result: The results of this research showed the distance of pollutant sources with the wells, the amount of pollutantsources, the physical condition of wells, and types of wells were significantly related to the levels of color, totalhardness, manganese, pH and organic matter of well water (t statistic value is 14.292). Well water quality of52,6% can be explained by environmental factorsConclusion: A total of 20 dug wells (100%) with the water quality that does not qualify as clean and drinkingwater. A total of 12 bore wells (60%) with the water quality that does not qualify as clean water. A total of 19 borewells (95%) with the water quality that does not qualify as drinking water.Key words: Water quality, dug wells, bore wells